Fatal Toxoplasma gondii Dissemination in a Heart Transplant Recipient: Description of a Case - S. Mastrobuoni; A. M. Dell'Aquila; J. Herreros (Case Reports in Transplantation)
A 45-year-old heart transplant recipient presented with fever, anorexia, asthenia, and lethargy. She had received heart transplantation only 5 weeks earlier for primary systemic amyloidosis with severe cardiac involvement. Serum sodium was low, and tacrolimus through level was high. Blood cultures and serology tests for infection were negative, and atypical pneumonia was suspected. Despite broad antibiotic, antiviral, and antifungal treatment, the patient clinical condition rapidly deteriorated and she died within three days of admission. Postmortem examination revealed a disseminated Toxoplasma gondii infection as a result of donor (+)/recipient(−) mismatch for Toxoplasma serology. Although very rare, toxoplasmosis in heart transplant recipient should be suspect in case of neurological deficit and respiratory symptoms. Prophylaxis treatment is recommended in case of mismatch.